Understanding the use of online role-play for collaborative argument through teacher experiencing: a case study. Issue 3 (26th May 2016) - Zhang, Li; Beach, Richard; Sheng, Yue
ABSTRACT: As computers and the Internet are increasingly employed in language teaching and learning, preparing teachers for the impending reality of online teaching is of paramount importance. This study investigated 10 in-service teachers participating in an online role-play as part of a digital education methods course to acquire an understanding of the use of online role-play for collaborative argument. The role-play lasted for 3 weeks and underwent three stages: preparation, implementation and reflection. Analyses of data gathered from the questionnaire survey, the class website for role-play, the blogs and the interviews indicate that online role-play was an appropriate way for teaching collaborative argument given that the topics were well-chosen and well-prepared, and that asynchronous role-play was more helpful than the synchronous role-play given the challenge of tracking the development of ideas. Benefits and problems of online role-play through synchronous chat were analysed and solutions were discussed. The research provides a new perspective on how teachers can be educated to integrate technology into their language instruction through their own experience of learning.